2010
DOI: 10.1007/s11739-010-0499-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of short- and long-term outcome in patients with chronic non-specific neck pain undergoing an exercise-based rehabilitation program: a prospective cohort study with 1-year follow-up

Abstract: The aim of this study was to describe the clinical course of patients with chronic, non-specific neck pain undergoing a public health covered, exercise-based rehabilitation program and to identify predictors of poor outcome. A prospective cohort study was carried out on patients with non-specific neck pain (6 months or longer), referred by their general practitioner to a 6-session program, including education and individually tailored exercise. The primary outcome measure for the course of neck pain was the No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…[8,9] Specifically, previous studies have been reported that pain catastrophizing is associated with increased pain intensity, disability, lower pain threshold/tolerance levels, poor prognosis, and a poor response to pain interventions in neck pain conditions. [913] …”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Specifically, previous studies have been reported that pain catastrophizing is associated with increased pain intensity, disability, lower pain threshold/tolerance levels, poor prognosis, and a poor response to pain interventions in neck pain conditions. [913] …”
Section: Introductionmentioning
confidence: 99%
“…Finally, as already mentioned, we did not thoroughly investigate the occurrence of anxiety and depression and life satisfaction that may have provided us more insight into a correlation with pain [41]. Moreover, while exploring catastrophism, which has been shown to be strongly associated with pain as well as with a poor rehabilitation outcome [42], we used only a single question rather than the complete tool [18], thus possibly limiting the sensitivity and specificity of our findings in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…The main goal of undergoing treatment, according to the patient, was investigated with an open question (''what is your main objective in undergoing this rehabilitation treatment?'') Other questions concerned expectations regarding the treatment; life satisfaction [16] and catastrophism, scored with a question taken from the Pain Catastrophizing Scale [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…Neck pain is one of the most common musculoskeletal disorders and can have a significant impact on people's ability to work and carry out activities of daily living [1][2][3][4][5][6][7][8][9]. The 2010 Global Burden of Disease study ranked neck pain as the fourth highest cause of disability, as measured by years lived with disability (YLDs) [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Neck pain is one of the most common musculoskeletal disorders and can have a significant impact on people's ability to work and carry out activities of daily living [1][2][3][4][5][6][7][8][9]. The 2010 Global Burden of Disease study ranked neck pain as the fourth highest cause of disability, as measured by years lived with disability (YLDs) [2][3][4][5][6][7][8][9][10]. Furthermore, the annual prevalence of neck pain amongst the general population is reported to be around 30-50%, leading to a significant health and economic burden within today's society [3,5,[7][8][9][11][12][13].…”
Section: Introductionmentioning
confidence: 99%